2021
DOI: 10.3390/ijerph18041689
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Activity and School Physical Education in Enhancing School Satisfaction and Life Satisfaction

Abstract: The aim of this study was to understand the role of school satisfaction on life satisfaction, according to gender, age, body mass index (BMI), and physical activity (PA) level. This was a cross-sectional descriptive study, carried out on 2823 adolescents (1396 boys and 1427 girls), aged between 12 and 16. A specific questionnaire to measure life satisfaction (Brief Multidimensional Student Life Satisfaction Scale (BMSLSS)), a questionnaire to measure satisfaction with school (“Life circumstances of Young peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 77 publications
0
11
0
2
Order By: Relevance
“…A pesar de que la Educación Física es un entorno facilitador para el aprendizaje y consolidación de conocimientos sobre hábitos saludables (Lirola et al, 2021;Moral-Garcia et al, 2021). Baker et al…”
Section: Resultsunclassified
“…A pesar de que la Educación Física es un entorno facilitador para el aprendizaje y consolidación de conocimientos sobre hábitos saludables (Lirola et al, 2021;Moral-Garcia et al, 2021). Baker et al…”
Section: Resultsunclassified
“…From this perspective, a promising avenue in research has been the investigation of students' health behaviors and their association with adaptive outcomes related to mental health and school success. For example, participation in physical activity was associated with reduced emotional problems (Bell et al, 2019), reduced psychological distress (Guddal et al, 2019), and increased school satisfaction (Moral‐Garcia et al, 2021) in adolescents. Other research has identified recreational screen time (e.g., Sampasa‐Kanyinga et al, 2020; Sánchez‐Miguel et al, 2023), sleep quality (e.g., Blake et al, 2017; Musshafen et al, 2021; Short et al, 2019), and dietary habits (e.g., Due et al, 1991; Hosker et al, 2019; Jacka et al, 2013; Kohlboeck et al, 2012; O'Neil et al, 2014; Valois et al, 2003) as additional factors that associate with mental health outcomes in school‐age youth.…”
Section: Introductionmentioning
confidence: 99%
“…The research study focuses on wearable, non-invasive technologies, which measure human stress levels utilizing numerous parameters [6]. A study by Martinez et al reported a dramatic increase in patients with cognitive load and anxiety in recent years [7]. The study's author also addressed stress as one of the states, which have become epidemiologically more prevalent in most nations worldwide [8].…”
Section: Introductionmentioning
confidence: 99%